2001
DOI: 10.3171/jns.2001.95.4.0601
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of progression-associated chromosomal aberrations for the prognosis of meningiomas: a retrospective study of 198 cases

Abstract: The cytogenetic classification of meningiomas provides a significant contribution to the predictability of tumor recurrence and is, therefore, a valuable criterion for the neurosurgeon's postoperative management protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
75
0
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 44 publications
13
75
0
5
Order By: Relevance
“…Some authors reported that meningiomas with chromosome 1p loss show the higher rate of recurrence occurring independently from the histological classification. [7][8][9] In our series, some lowgrade meningiomas had FISH 1p definitive deletion and 19q monosomy or polysomy. Further investigation is needed to determine whether these low-grade meningiomas with chromosomal abnormality have high rates of recurrence and progression.…”
Section: Discussionsupporting
confidence: 44%
“…Some authors reported that meningiomas with chromosome 1p loss show the higher rate of recurrence occurring independently from the histological classification. [7][8][9] In our series, some lowgrade meningiomas had FISH 1p definitive deletion and 19q monosomy or polysomy. Further investigation is needed to determine whether these low-grade meningiomas with chromosomal abnormality have high rates of recurrence and progression.…”
Section: Discussionsupporting
confidence: 44%
“…In a previous study, we classified 198 consecutive meningiomas into four groups according to their karyotypes [4]. We found a very strong correlation between the cytogenetic findings and the rates of tumor recurrence.…”
Section: Discussionmentioning
confidence: 74%
“…Cytogenetic aberrations of meningiomas have later been shown to be significantly associated with the tumor location as well. Nearly half of the meningiomas of the cranial vault display progression-associated chromosome aberrations [4]. In 1980, Zankl and Zang showed that meningiomas of the skull base typically present with 46 chromosomes, whereas those of the convexity have significantly more chromosome aberrations [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Ketter, et al, 11 stated that all spinal meningiomas in their series (23 of 198) had a normal chromosomal set or a monosomy of 22. This genotype was not associated with disease recurrence, in contrast to intracranial meningiomas, which had a higher rate of tumors with multiple chromosomal aberrations, correlating with higher rates of recurrences.…”
Section: Genetic Alterationsmentioning
confidence: 94%